Registros de melanismo en Sebastes oculatus (Perciformes, Scorpaenoidei: Sebastidae) en la costa norte de Chile - Avilés, Jorge; Vargas, Fernando; Flores, Héctor (Revista de Biología Marina y Oceanografía, 2023)
Melanism is the presence of an excess of dark pigmentation in an animal, which causes a total or partial blackening of the skin. In fish, melanosis has been reported for a few species, indicating that it is not a common aspect and that it more frequently affects limnic species. The capture of a Sebastes oculatus female specimen, with complete melanism, is reported. The individual was captured by hand line, in the town of Isla Pájaro II, northern Chile. Its standard length is 31.5 cm and its total weight is 993 g. The general coloration of the body is dark gray. The fins do not have the orange hue characteristic of the species at their ends. The melanic condition in S. oculatus is very rare, it is the second time that it has been reported for this species, where the expression of a dark color would be beneficial for specimens that inhabit bottoms with little vegetation and between cracks.